Being a university student in the field of institutional forces - Marta Panaia (Universitat Politècnica de València, 2015)
The university student being is an evolution in time, which is limited and encouraged by a force field that sets limits and freedoms. This process varies constantly as cognitive bases,  specialties  and  regions  and  the demands of the labor market.In  its  definition  refers  to  the  teacher-student dyad and the institution in which the student is formed in a broader context, city, region, state.The  reflections  presented  here,  arising from  the  survey  paths  leavers  and engineering students in different regions of Argentina. So they are not generalizable to other professions, but have the advantage of capturing processes change over time by means of longitudinal and biographical techniques and having methodologically comparable surveys in different regions and specialties of engineering, including differentiating the traditional engineering of technology and new engineering. The education process is defined as a co-production  of  three  characteristics  and the  main  criticisms  raised  with  other theoretical frames. A dynamic process that changes over time and is no stranger to the institutional field in which it occurs is considered. One  during  the  first  years  where  the applicant in student and the second where the student already assumed as such begin to think about their forms of employability and define a project in the labor market becomes:  Finally  the  formation  of  two profiles arises.